Geographical Access to Point-of-care diagnostic tests for diabetes, anaemia, Hepatitis B, and human immunodeficiency virus in the Bono Region, Ghana - Ansu-Mensah, Monica; Ginindza, Themba G.; Amponsah, Samuel Kofi; Shimbre, Mulugeta Shegaze; Bawontuo, Vitalis; Kuupiel, Desmond (BMC health services research, 2024)
Background Diabetes mellitus, human immunodeficiency virus (HIV), hepatitis B and anaemia are major global public health issues according to the World Health Organization (WHO). Access to diagnostic testing is essential for their prompt detection and treatment. The WHO has recommended a list of essential in-vitro diagnostics for testing at all levels of care. However, a survey preceding this study showed limited availability of point-of-care (POC) tests for these conditions in the Bono Region (BR) of Ghana. This study assessed the geographical access to diabetes, anaemia, hepatitis B, and HIV POC testing in the BR, Ghana for targeted improvement. Methods We gathered the geolocated data of 137 facilities (CHPS, Clinics, healthcare centres, and hospitals) in the BR that were providing glucose, haemoglobin (Hb), Hepatitis B Surface Antigen (Hep B), and HIV POC testing services in July 2022. We used ArcGIS 10.1 to quantify the geographical access (distance and travel time) to the nearest available testing site for each test and show places with inadequate access, for targeted improvement. The journey time was calculated assuming a speed of 20 kilometres (km)/h. ArcMap 10.1 was employed to run spatial autocorrelation (Moran Index (MI)) to determine the spatial distribution of the facilities providing the tests investigated. Results Of the 137 facilities, the glucose test was available in 67 (49%), the Hb test in 55 (40%), the Hep B test in 44 (32%), and the HIV test in 73 (53%). The mean (standard deviation (SD)) for obtaining glucose tests in the region was 7.4 ± 3.7 km, Hb was 8.1 ± 4.06 km, Hep B was 8.2 ± 4.1 km, and HIV test was 7.3 ± 3.7 km by a motorised cycle. The mean SD travel time in the region to obtain the glucose test was 94.4 ± 47.2 min compared to 95.7 ± 47.8 min for Hb, 95.9 ± 47.93 min for Hep B, and 92.7 ± 46.3 min for the HIV test. Three districts (Berekum East, Dormaa East, and Jaman North) recorded shorter distances (< 10 km) and a shorter travel time to the glucose, Hb, Hep B, and HIV tests compared to the Banda district, which recorded more than 10 km for all tests investigated. Positive IM values were recorded for all the POC tests, suggesting that the health facilities providing the glucose, Hb, Hep B, and HIV tests in the BR were spatially distributed at random. Conclusions The findings revealed moderate access to all the tests in districts across the region. However, geographical access to glucose, Hb, Hep B, and HIV POC testing was poor (distance ≥ 10 km and travel time of ≥ 93 min), in the Banda district. This study showed the need to prioritise the Banda district for targeted improvement for all the tests. A further study is recommended to identify potential solutions to addressing the POC testing implementation in the BR, as demonstrated by this study.